Predicting Progression to Mild Cognitive Impairment - Petersen, Ronald C. (Ann Neurol, 2019)
Despite much attention to the use of biomarkers for predicting Alzheimer’s disease, little information is available at the individual level. We used the population-based Mayo Clinic Study of Aging to estimate absolute risk of cognitive impairment by biomarker group. Risk increased with age and any biomarker abnormality. For example, a 75-year-old with abnormal amyloid and cortical thinning biomarkers has ≈20% chance of cognitive impairment by age 80 whereas with normal biomarkers the chance is <10%. Persons with only one abnormal biomarker had similar intermediate risks.